Oncology patient preferences for depression care: A discrete choice experiment. Issue 4 (21st February 2019) - Hobden, Breanne; Turon, Heidi; Bryant, Jamie; Wall, Laura; Brown, Scott; Sanson‐Fisher, Rob
Abstract: Objective: Using a vignette‐style DCE in a sample of oncology patients, this study explored: (1) the relative influence of the patient's level of concern about their depression on preferences for care, (2) the relative influence of depression severity according to a mental health checklist on preferred treatment‐seeking options, and (3) whether patient age and gender were associated with depression care preference. Methods: A discrete choice experiment (DCE) survey of cancer patients was conducted. Hypothetical vignettes to elicit care preferences were created using two attributes: the cancer patient's level of concern about depression (a little or a great deal) and results of a mental health checklist (not depressed or very depressed). Three response options for care preferences were presented, including a self‐directed approach, shared care approach, and clinician‐directed referral approach. Participants chose their most and least preferred options. Results: A total of 281 cancer patients completed the survey. There was a significant association between level of concern and the most preferred option. Those with a great deal of concern about depression preferred to receive referral from their clinician more than those with a little concern about depression. Males were significantly more likely to select a self‐directed approach as their most preferred option. Conclusions: An oncology patient's level of concern about depression may influence the type of care they want to receive from their cancer doctor for depression. This finding has implications for depression screening in clinical practice.